1998
DOI: 10.3171/jns.1998.88.5.0817
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic treatment of carpal tunnel syndrome: a critical review

Abstract: Success and complication rates of endoscopic carpal tunnel release surgery are similar to those for standard open procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(33 citation statements)
references
References 51 publications
0
32
0
1
Order By: Relevance
“…13,[28][29][30] Some of these studies showed that CTR provides early relief of sensory symptoms such as pain and sensory disturbance, which are the most common symptoms of median nerve compression. [13][14][15]31 In our study, 12 of the 13 patients felt sensory symptomatic relief 5.38 weeks after CTR with significant improvement in static or moving 2PD tests following surgical release of the transverse carpal ligament (Table 1). This result is similar to Yung's findings that patients receiving a limited incision of the ligament experienced improved movement in the 2PD test at 4 weeks postsurgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,[28][29][30] Some of these studies showed that CTR provides early relief of sensory symptoms such as pain and sensory disturbance, which are the most common symptoms of median nerve compression. [13][14][15]31 In our study, 12 of the 13 patients felt sensory symptomatic relief 5.38 weeks after CTR with significant improvement in static or moving 2PD tests following surgical release of the transverse carpal ligament (Table 1). This result is similar to Yung's findings that patients receiving a limited incision of the ligament experienced improved movement in the 2PD test at 4 weeks postsurgery.…”
Section: Discussionmentioning
confidence: 99%
“…12 Using sensory measurement tools, and particularly sensory threshold measurements, previous studies imply that sensory symptoms are quickly relieved by carpal tunnel release (CTR). [13][14][15] However, few studies investigated the effect of sensory improvement upon manual capacity after therapy or surgery. Among the previous studies addressing this area, one uses a rapid pinch-and-release task to assess manual task functions of CTS patients who underwent surgery.…”
mentioning
confidence: 99%
“…The advantages and disadvantages of the above techniques are a matter of debate, but their common goal is to release the median nerve by completely transecting the flexor retinaculum (FR) [5][6][7][8][9][10] . Whatever the technique, important structures such as the palmar cutaneous, recurrent motor and digital branches of the median nerve and the ulnar nerve, the superficial palmar arch and tendons must be protected during the operation 9 .…”
mentioning
confidence: 99%
“…Other literary sources do not suggest this (3,8). A metaanalysis of randomized controlled trials (17) shows a reduction in scar tenderness and increase in grip and pinch strength at 12 week follow up in endoscopic group but also increases susceptibility to reversible nerve injury that is three times as likely to occur with endoscopic carpal tunnel release than with open carpal tunnel release.…”
Section: Tabmentioning
confidence: 99%